The unwomanly face of war : an oral history of women in World War II - Aleksievich, Svetlana, 1948- (Random House, 2017)
"Bringing together dozens of voices in her distinctive style, War's Unwomanly Face is Svetlana Alexievich's collection of stories of women's experiences in World War II, both on the front lines, on the home front, and in occupied territories. This is a new, distinct version of the war we're so familiar with. Alexievich gives voice to women whose stories are lost in the official narratives, creating a powerful alternative history from the personal and private stories of individuals. Collectively, these women's voices provide a kaleidoscopic portrait of the human side of the war. When the Swedish Academy awarded Svetlana Alexievich the Nobel Prize in Literature, they praised her "polyphonic writings, a monument to suffering and courage in our time," and cited her for inventing "a new kind of literary genre." Sara Danius, the permanent secretary of the Swedish Academy, added that her work comprises "a history of emotions -- a history of the soul."--Provided by publisher.